Comparison of Cerebral Embolic Events Between Right and Left Upper Extremity Access During Fenestrated/Branched Endovascular Aortic Repair. (February 2021) - Mirza, Aleem K.; Tenorio, Emanuel R.; Marcondes, Giulianna B.; Lima, Guilherme B. B.; Macedo, Thanila A.; Mendes, Bernardo C.; Oderich, Gustavo S.
Purpose: To evaluate the incidence and outcomes of cerebral embolic events when using right (RUE) vs left upper extremity (LUE) access for fenestrated/branched endovascular aneurysm repair (f/bEVAR). Materials and Methods: A retrospective review was conducted of 290 consecutive patients enrolled in a physician-sponsored Investigational Device Exemption study to evaluate f/bEVAR between 2013 and 2018. Of these, 270 patients (93%) had an upper extremity access with 12-F sheaths, including 205 patients (mean age 75±8 years; 147 men) with LUE and 65 patients (mean age 73±8 years; 42 men) with RUE access. Outcome measures were technical success, procedural metrics, major adverse events (MAEs), any stroke or transient ischemic attack (TIA), and mortality. Results: Technical success was higher (p=0.04) for LUE (99.6%) vs RUE access (98.4%). Patients treated via RUE access more often had extent I-III thoracoabdominal aortic aneurysms (57% vs 39%, p=0.03). Procedural metrics were similar for LUE vs RUE sides, including endovascular time (255±80 vs 246±83 minutes, respectively; p=0.23), fluoroscopy time (84±32 vs 90±35 minutes, respectively; p=0.80), and contrast volume (156±57 vs 153±56 mL, respectively; p=0.82). Total radiation exposure was significantly higher for LUE vs RUE access (2463±1912 vs 1757±1494 mGy, respectively; p=0.02). There were 2 deaths (1%) at 30 days or during hospital admission, both unrelated to access site complications. MAEs occurred in 32% of patients who had LUE and 26% of those who had RUE access (p=0.44). Five patients (2%) had embolic stroke and none had TIA. Embolic strokes were ipsilateral to the access side in 4 patients and affected the posterior circulation in 3. Two patients (1%) had hemorrhagic strokes. The incidence of stroke was 3% for LUE and 2% for RUE access (p>0.99). Conclusion: Fenestrated/branched stent-graft repair was associated with low rates of cerebral embolic events and no significant difference between the right vs left upper extremity approach.